PD operads and explicit partition lie algebras - Brantner, L; Campos, R; Nuiten, J (American Mathematical Society, 2024)
Infinitesimal deformations are governed by partition Lie algebras. In characteristic 0, these higher categorical structures are modelled by differential graded Lie algebras, but in characteristic p, they are more subtle.